The Characteristic Analysis of Characters in Gatotkaca Gandrung Dance by R. Ono Lesmana Kartadikoesoemah - Sarah Sampepadang; Trianti Nugraheni; Putri Lilis Dyani (Jurnal Seni Tari, 2023)
It started with the appreciation of a dance artist from Sumedang, R. Ono, for the Gatotkaca Gandrung dance in the Solo style. Then, he attracted his attention to create a Gatotkaca Gandrung dance piece in the Kasumedangan style. Different from the Solo style, the dance created by R. Ono is played by four dancers, namely Gatotkaca, Pergiwa, Pergiwati, and Cakil, with their distinctive characters full of meaning in life. The purpose of this research is to analyze the characteristics of the characters in the Gatotkaca Gandrung dance by R. Ono through the study of choreography, makeup, and costume. This study used a descriptive analysis research method using a qualitative approach. The researchers collected data using observation, interviews, documentation, and literature study. The data obtained is analyzed by reducing the data, presenting the data in narrative form, and drawing conclusions. The results obtained are Gatotkaca, as the main character, has the character of monggawa lungguh from his hiber movement, makeup, and costumes reflecting his independence, strength, toughness, responsible, courage, sacrifice, agility, and calmness in dealing with problems. Pergiwa and Pergiwati, as supporting characters, have the character of putri lungguh who reflects a graceful and cheerful nature. In addition, Cakil is a symbol of the lust of human anger. As a supporting actor, he also reflects the nature of cunning, mischievous, crotchety, agile, and brave. This character research can be used as an artistic reference in formal and informal learning that can be applied in life.